Arterial hypertension prevention as an actual medical and social problem (Bangladesh Journal of Medical Science, 2020)
Social changes, technological re-equipment, intensive formation of urban infrastructure have led to a constant increase in stress factors and an excessive growth of the nervous and psychological population burden. As a result of these processes in economically developed countries, acute diseases are becoming less and less significant, unlike the group of chronic disorders, such as arterial hypertension. Data from the review of the literature and the data we have received indicate that there is an increase in the level of cortisol in the blood in the phase of anxiety, which reduces in the resistance phase. A significant role is played by another hormone - insulin, which plays a key role in the development of the general adaptive syndrome. Through it the body implements numerous counter-defects in relation to the regulatory influence of catecholamines and cortisol. In conditions of prolonged stress, the level of insulin in the blood decreases and diabetes develops. The effect of cortisol and catecholamines in the resistance phase persists. The level of oxidative modification of blood plasma proteins indices depends on the behavior of the individual and changes in his psycho-emotional state, while a prolonged increase in the levels of catecholamines and cortisol in peripheral blood causes the development of psychosomatic pathology. It is proved that under the influence of complex action of risk factors there are significant changes in the psycho-emotional state that cause hypertension. This is confirmed by the presence of the highest level of reactive anxiety in patients with hypertension of the 1st stage on the background of the lowest personal anxiety which is the basis for the occurrence of the disease. With the progression of hypertension there are more profound changes in the personality of the patient, which is accompanied by the accumulation of personal anxiety, which can lead to a depressive state of neurotic genesis, which we observed with its complication. On the basis of a comprehensive study, the effect of stress on the occurrence of a syndrome of psychoemotional stress is shown, which leads to a steady increase in blood pressure - hypertension, and with its subsequent action complicates its course.Bangladesh Journal of Medical Science Vol.19(4) 2020 p.722-729